Hospital Responsibility for Negligence of Medical Personnel to Patients - Yohanes Hendrikus Hugu Liwun (Budapest International Research and Critics University, 2022)
This legal research aims to find out how the hospital's legal responsibility for the negligence of medical personnel in carrying out medical actions against patients in hospitals. This research is a prescriptive normative legal research. The approach used in this research is the statute approach. The types of legal materials used in this study are primary and secondary legal materials. The method of collecting legal materials used in this research is through a literature study and then analyzed by the method of deduction, analysis to draw conclusions from general things to specific things. legal relationship between medical personnel and hospitals according to several relevant laws and regulations, namely Law Number 29 of 2004 concerning Medical Practices, Law Number 44 of 2009 concerning Hospitals, Law Number 36 of 2014 concerning Health Workers, Law Number 13 of 2003 concerning Employment, and the Hospital Code of Ethics, it can be concluded that the relationship between hospitals and medical personnel is based on the existence of an employment relationship. The working relationship between medical personnel and hospitals determines the hospital can be responsible. Hospitals are responsible for acts of negligence of medical personnel that cause harm to patients can be determined based on Article 1367 of the Civil Code, and Article 46 of Law Number 44 of 2009 concerning Hospitals, which states that hospitals are responsible for acts of negligence committed by medical personnel